MARINE ALGAL STEROL HYDROCARBON WITH ANTI-INFLAMMATORY, ANTICANCER AND ANTI-OXIDANT PROPERTIES - EMAN A. IBRAHIM; HANAN F. ALY; DOHA H. ABOU BAKER; KHALED MAHMOUD; FAROUK K. EL-BAZ (International Journal of Pharma and Bio Sciences, 2016)
Important ingredients, various bioactivities, biomaterials are derived from marine algae which are used in many products, such as cosmetics and drugs for treating cancer and other diseases. The present research deals with studying the sterol hydrocarbon content of Taonia atomaria brown algae and their related biological activities as anti-inflammatory, anticancer activities against different cancer cell lines including; colon cancer cell line (HCT116), breast cancer cell line (MCF7), liver cancer cell line (HePG2) and ovarian cancer cell line (A549). The determination of antioxidant, scavenging activity of T. atomaria sterol fraction and Total Antioxidant Capacity (TAC) were also being elucidated. The present results clearly indicated the presence of hexacosane (C26) sterol hydrocarbon with the highest percentage (21.78%), followed by campasterol (C28:20.66%) and nonadecane (C19:18.06%) in addition, cholesterol, β-sitosterol and pentadecane showed 15.92, 14.07 and 9.523%, respectively. Moreover, sterol fraction exhibited anti-inflammatory and anticancer activities in a dose dependent manner as well as it exhibited powerful DPPH free radical scavenging activity due to its high level of total antioxidant capacity. Thus, it could be concluded that, natural products as sterol hydrocarbon fraction derived from T. atomaria marine algae protects cells by modulating the effects of oxidative stress. Because oxidative stress plays an important role in inflammatory reactions and in carcinogenesis, marine algal natural products have a potential role for use in anticancer and anti-inflammatory drugs.